Hierarchical superstructures of norbornene-based polymers depending on dendronized side-chains. Issue 33 (5th August 2016) - Kim, Dae-Yoon; Kang, Dong-Gue; Shin, Suyong; Choi, Tae-Lim; Jeong, Kwang-Un
Abstract : For understanding the self-assembly behaviours of norbornene-based main-chain polymers depending on side-chain pendants, a series of polynorbornenes containing the programmed dendrons is newly designed and successfully synthesized via ring opening metathesis polymerization. Abstract : For understanding the self-assembly behaviors of norbornene-based main-chain polymers depending on dendronized side-chains, a series of polynorbornenes containing the programmed dendrons (AT3 P and BP3 P) is newly designed and successfully synthesized via ring-opening metathesis polymerization (ROMP) with high molecular weights and narrow polydispersity indices. The phase transitions and molecular packing structures of AT3 P and BP3 P are investigated by the combination of thermal, scattering and microscopic analyses. AT3 P with flexible and hydrophobic alkyl chain dendrons forms the columnar nematic (ColN ) liquid crystal (LC) phase. By introducing a rigid biphenyl mesogen and a hydrophilic triethylene oxide linker between the hydrophobic alkyl chain and the polynorbornene main-chain, a smectic A (SmA) LC phase is formed, mainly due to the nanophase separations and the strong intermolecular interactions between the biphenyl mesogens. This study reveals that the hierarchical superstructures of norbornene-based polymers can be precisely controlled by tuning the chemical structures and the physical interactions of side-chain pendants.